Specialized Mobile Applications as Means of Optimizing the Power Supply System of the Republic of Belarus - M. I. Fursanov; P. A. Sazonov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2020)
The active development of the mobile platforms sector such as smartphones, smart watches, fitness bracelets and other wearable electronic devices in the last 4 years has caused a huge growth of the market of mobile applications-services. Western countries are actively implementing mobile applications-services for household energy users. In Belarus, there is a positive dynamics in the number of active users of applications-services, every year it is possible to attract 7 % of unique customers. In the present paper the experience of implementation and operation of the mobile application for power systems is analyzed. The dynamics of the market of mobile applications-services has been traced: the amount of time spent by the person in interaction with the device was determined as well as the total expenditure of funds in the application at the moment; also, the growth of expenses within the applications was forecasted. The potential benefits for business and end-users of services from the implementation of mobile applications-services were demonstrated. Their properties, main qualities and advantages over traditional methods of “business – client” interaction are considered. A number of features needed for the successful functioning of the mobile application in the power system of Belarus are identified. The process of creating software for smart devices has been studied and the functionality needed by the mobile application for the power system has been proposed for attracting new users. A special algorithm for the launch and successful “life cycle” of a mobile application has been proposed. It allows to operate and develop mobile applications-services as efficiently as possible, as well as to avoid the most common errors at the stages of their development and launch. The implementation of a mobile application in the power system of the Republic of Belarus, in the long-term, will significantly increase customer loyalty, simplify interaction with users, make it possible to build new models of distribution of electricity, and, consequently, regulate the demand for energy resources.